IRON CONTAINING MINERALS IN THE BIOX PROCESS - Nurmurodov, To‘lkin Isomurodovich; Saidova, Nodira Urol kizi (INTERNATIONAL CONFERENCES, 2022)
As a result of biooxidation, iron-containing minerals are formed, including jarosite, iron arsenate, goethite and other minerals. Jarosite is a relatively rare iron hydroxosulfate mineral. Interest in jarosite mineral has been growing in recent years. Jarosite plays an important role in acid mine drainage (AMD) pollution. AMD pollution, that is, the release of toxic metals into the environment, occurs as a result of any mining process.